PRODUCTION OF ANTIBODY AGAINST DOMOIC ACID IN NEW ZEALAND WHITE RABBIT - Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2016)
In order to develop an ELISA KIT for detection of domoic acid in seafood in Vietnam, the antibody against domoic acid was produced by immunizing in New Zealand white rabbit using 250 and 500 µg domoic acid-dissuccinyl substrate-bolvine serum albumin as an antigen. Using 500 µg of domoic acid-dissuccinyl substrate-bolvine serum albumin, antibody exhibited activity in the rabbit’s serum after 5 months and only one out of 4 rabbits showed high activity (OD>3,000). Antibody activity in the rabbit serum was increasing and reached maximum after 6 months of experiment, then decreased rapidly in the following months. Domoic acid antibody titer was wide in range with good correlation in 1/800 to 1/51200 dilution. In 1/12800 dilution, a background signal was very low, with clear distinction between negative and positive results, so this concentration was chosen as an antibody titer unit. This unit is rather lower than that in some other studies, however, antibody obtained in this study showed no cross action with any of kainic acid, aspartic acid, glutamic acid, gamma-aminobutyric acid, globulin, proline, hydroxyproline, which have similar chemical structure to domoic acid. The results showed that antibody obtained in the study is specific to domoic acid, and can be used as material for domoic acid-ELISA kit in Vietnam.